2016
DOI: 10.1200/jco.2016.34.2_suppl.387
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary utilization trends and survival outcomes in patients undergoing radical cystectomy and bladder preservation therapy for muscle invasive bladder cancer.

Abstract: 387 Background: To compare overall survival (OS) in patients undergoing radical cystectomy (RC) and bladder preservation therapy (BPT) for muscle invasive urothelial carcinoma of the bladder. Methods: We conducted a retrospective, observational cohort study in which we reviewed the National Cancer Database (NCDB) to identify patients with analytic stage II-III (N0M0) urothelial carcinoma of the bladder from 2003-2011. BPT patients were stratified as any external beam radiotherapy (EBRT), definitive radiothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…38 Improved OS in patients undergoing RC was noted regardless of BPT definition used following adjustment. 38 38 These cohort analyses elucidate that careful patient selection may provide similar survival outcomes after accounting for measured and unmeasured confounding biases when comparing BPT to RC. 37,38 The authors recognize the shortcomings of BPT, including the utilization of clinical staging, which is considered inferior to RC pathologic staging.…”
Section: Survival Outcomesmentioning
confidence: 95%
See 3 more Smart Citations
“…38 Improved OS in patients undergoing RC was noted regardless of BPT definition used following adjustment. 38 38 These cohort analyses elucidate that careful patient selection may provide similar survival outcomes after accounting for measured and unmeasured confounding biases when comparing BPT to RC. 37,38 The authors recognize the shortcomings of BPT, including the utilization of clinical staging, which is considered inferior to RC pathologic staging.…”
Section: Survival Outcomesmentioning
confidence: 95%
“…38 38 These cohort analyses elucidate that careful patient selection may provide similar survival outcomes after accounting for measured and unmeasured confounding biases when comparing BPT to RC. 37,38 The authors recognize the shortcomings of BPT, including the utilization of clinical staging, which is considered inferior to RC pathologic staging. Agreement between clinical and pathologic staging was demonstrated in only 35.7% of patients in a 2006 multi-centered international series.…”
Section: Survival Outcomesmentioning
confidence: 98%
See 2 more Smart Citations
“…There is no randomized controlled trial comparing outcomes between BPT and RC in MIBC patients. Recently, 3 studies retrospectively compared prognosis of MIBC patients between BPT and RC using a propensity score matching analysis: 2 studies derived from the National Cancer Database (NCD) [18,19] and one study from a Canadian multidisciplinary bladder cancer clinic [20]. The 2 NCD studies demonstrated more favorable OS for RC than that for BPT.…”
Section: Indicationsmentioning
confidence: 99%